Inter-population variation in germination characteristics of "Plantago lanceolata" seeds: effects of temperature, osmotic stress and salinity - Mira, Sara; Veiga-Barbosa, Luciana; González-Benito, M. Elena; Pérez-García, Félix (Mediterranean Botany, 2018)
Plantago lanceolata is a perennial herbaceous plant widely distributed throughout the Mediterranean region. Variation in germination requirements and tolerance to osmotic stress and salinity were tested using seeds from two wild populations. Germination experiments were conducted under controlled conditions at constant (15, 20 and 25ºC) and alternating (20/10 and 25/15ºC) temperatures, and under a 16 h/8 h light/dark photoperiod. Seeds of both populations were non-dormant and incubation temperature significantly affected the final germination percentage and germination rate. Germination percentages ranged from 27 to 85% for the different temperatures and populations. Significant inter-population variation was found for the germination percentages reached at alternate temperature regimes. To determine the effect of osmotic stress and salinity, four polyethylene glycol (PEG 6000: 10, 20, 30 and 40% w/v) and four NaCl concentrations (50, 100, 200 and 300 mmol·L-1) were tested. Seed germination significantly decreased with increasing in PEG and NaCl concentration. Seed germination recovery when they were transferred to distilled water after PEG or salinity treatments was variable depending on population, suggesting that P. lanceolata seeds are moderately tolerant to osmotic and salt stresses at germination stage.